Recognizing the demand for emergency medical services during the Songkran Festival, Thailand’s intangible cultural heritage: an approach for healthcare policy development - Korakot Apiratwarakul; Lap Woon Cheung; Dhanu Gaysonsiri; Kamonwon Ienghong (Critical Public Health)
The Songkran Festival, held in Thailand in (April 13–15 annually), has been recognized as an intangible cultural heritage by the UNESCO. This mass gathering event attracts 250,000 people daily. However, there has been a lack of previous studies demonstrating the emergency medical services (EMS) utilization pattern during this festival. The aim of this study was to evaluate EMS response times, comparing the Songkran Festival periods with the routine daily activity. This retrospective database analysis was conducted using data from Thailand’s EMS at Srinagarind Hospital between April 2023 and April 2024. Data collected EMS operation time, the characteristics and medical resources used during the Songkran Festival. 2,622 EMS missions were examined. The time of EMS missions were most frequent during the sunset hours (6 PM to 6 AM) in the Songkran group. During the festival, EMS usage was significantly higher than routine services (P < 0.001). The average response time during the Songkran period (12.20 mins) was significantly longer, than the routine period (9.10 mins, P = 0.024). The Songkran Festival affected EMS utilization. The response and on scene times in EMS were longer than those during routine services. Health organizations researching to improve EMS during significant mass gathering events are urged to embrace the themes obtained in this study.